KETERKAITAN DUKUNGAN SUAMI TERHADAP PARTISIPASI PEREMPUAN HAMIL DALAM KELAS IBU HAMIL: KETERKAITAN DUKUNGAN SUAMI TERHADAP PARTISIPASI PEREMPUAN HAMIL DALAM KELAS IBU HAMIL (LPPM STIKes Buleleng, 2018)
The background of writing this article is based on the results of previous research that severalclasses of pregnant women have been prepared by the government both at the community healthcenter (Puskesmas)and at the Maternal and Child health Service (posyandu) but it has not beenutilized optimally. This is evidenced by the participation of pregnant women in this program isstill quite low. This article aims to determine the relationship between husband's support with theparticipation of pregnant women in the utilization of the class of pregnant women. The methodused is a literature study or study results from the results of previous researches. The resultsshow that husband's support has a significant influence. Pregnant women who have the supportof their husbands are more likely to take classes in pregnant women than those who are notsupported. Based on the analysis, it can be concluded that husband's support will increase theparticipation of pregnant women in the class of pregnant women. The increment of husband'ssupport for both primi and multi gravida is needed in increasing the participation of pregnantwomen in the class of pregnant women.